Synthesis and properties of phthalonitrile terminated polyaryl ether nitrile containing fluorene group. Issue 34 (14th May 2018) - Wang, Guangxing; Guo, Ying; Li, Zheng; Xu, Shuangshuang; Han, Yue; Luo, Zhenhua; Ye, Li; Zhou, Heng; Zhao, Tong
ABSTRACT: A series of phthalonitrile terminated polyaryl ether nitrile oligomers containing fluorene group (BPPENs) were synthesized and cured in the presence of bis[4‐(4‐aminophenoxy)phenyl]sulfone. Additionally, the quartz fiber reinforced composites were prepared by hot‐pressing process. The structure of oligomers was characterized by 1 H‐NMR and GPC. The curing behavior of BPPENs was studied by DSC, IR, and rheological tests in detail. Thermal stability and mechanical properties were also investigated. The results showed that the oligomers showed excellent solubility. BPPENs could be dissolved in common solvents at ambient temperature. TGA and DMA results showed that the cured polymer and composites possessed excellent thermal properties with high residual weight of 72.4% at 1000 °C and 5% thermal degradation temperature ( T 5% ) of 548 °C under inert atmosphere. The bending strength of quartz fiber reinforced composites was about 500 MPa, exhibiting good mechanical property. The products could be used as high performance polymers or a modifier for heat‐resistant resins. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46606. Abstract :